Indigenous Festival dan Pembelajaran Gastronomi pada Program Studi Perhotelan - Abdillah, Fitri Abdillah; Ayuningsih, Sri Fajar; Rachmat, Timotius Agus (JURNAL GASTRONOMI INDONESIA, 2023)
The festival, for the Osing community, is a ritual activity to give thanks to the presence of God Almighty, and hope for a good future. In various ritual festival rituals, gastronomy is always involved as the main tool. This research aims to identify the development of Indonesian gastronomic learning through festivals of the Osing community in Banyuwangi. The Tumpeng Sewu and Barong Ider Bumi are the biggest ritual festivals.  The qualitative method is used to explore the captive fenomena and linked to gastronomy subject in hospitality study program.  The findings show that festival activities in the Osing community can be emulated in gastronomy subject by (1) including discussion of Indonesian gastronomy as the main subject; (2) the people of Osing Kemiren have genuine hospitality and can be adopted as Indonesian-style hospitality in service learning; (3) A gastronomic tour can be created as an attraction in the form of providing local natural raw materials, cooking, serving and eating procedures in the Osing version; (4) by adopting a knowledge management cycle, various ritual dishes can be made explicit by compiling various books about Osing dishes.  As implication, higher education has to implement in realizing explicit knowledge from local community wisdom to the sustainability.